Mixed-methods study to examine the response of opioid addiction treatment programmes to COVID-19: a study protocol - Sugy Choi; Rhea Naik; Kamila Kiszko; Charles Neighbors; Thomas D’Aunno (BMJ Open)
Introduction The COVID-19 pandemic is forcing changes to clinical practice within traditional addiction treatment programmes, including the increased use of telehealth, reduced restrictions on methadone administration (eg, increased availability of take-home doses and decreased requirements for in-person visits), reduced reliance on group counselling and less urine drug screening. This paper describes the protocol for a mixed-methods study analysing organisational-level factors that are associated with changes in clinic-level practice changes and treatment retention.Methods and analysis We will employ an explanatory sequential mixed-methods design to study the treatment practices for opioid use disorder (OUD) patients in New York State (NYS). For the quantitative aim, we will use the Client Data System and Medicaid claims data to examine the variation in clinical practices (ie, changes in telehealth, pharmacotherapy, group vs individual counselling and urine drug screening) and retention in treatment for OUD patients across 580 outpatient clinics in NYS during the pandemic. Clinics will be categorised into quartiles based on composite rankings by calculating cross-clinic Z scores for the clinical practice change and treatment retention variables. We will apply the random-effects modelling to estimate change by clinic by introducing a fixed-effect variable for each clinic, adjusting for key individual and geographic characteristics and estimate the changes in the clinical practice changes and treatment retention. We will then employ qualitative methods and interview 200 key informants (ie, programme director, clinical supervisor, counsellor and medical director) to develop an understanding of the quantitative findings by examining organisational characteristics of programmes (n=25) representative of those that rank in the top quartile of clinical practice measures as well as programmes that performed worst on these measures (n=25).Ethics and dissemination The study has been approved by the Institutional Review Board of NYU Langone Health (#i21-00573). Study findings will be disseminated through national and international conferences, reports and peer-reviewed publications.